DYNAMIC POWER CONTROL OF THE GRID CONVERTERS - Zieliński, Dariusz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
The dynamic growth of the renewable energy sources sector causes that the Energy Regulatory Office introduces stricter and stricter grid codes about quality of the energy and dynamics of the sources. In the future, grid codes will require that the dynamic properties of the renewable source of energy is similar to the synchronous generator with the same power. Moreover, the renewable source of energy should damp power oscillation in power grid, and support it to stabilize the voltage. These causes lead us to use a high dynamic nonlinear control system – converters, installed between a source and a power grid. The paper presents a nonlinear controller improves the dynamic power control of the vector inverters’ systems. The analysis was made by using the MATLAB/Simulink software.